Analisis Kapabilitas Internal dalam Proses Pengajuan Proposal Acara: Studi Kasus DAMN! Inc. - Sofia Aulia Difani; Aditya Rizki Rinaldi (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2026)
The Meetings, Incentives, Conventions, and Exhibitions (MICE) industry in Indonesia is growing rapidly, driving the proliferation of Event Organizer (EO) companies, yet an EO's success in securing projects depends heavily on the internal capabilities that support a competitive pitching process. This study analyzes the internal capabilities of DAMN! Inc and their contribution to each stage of the pitching process, while also evaluating their strategic value as a source of competitive advantage. A descriptive qualitative approach with a single case study method was employed. Data were collected through triangulation of semi-structured interviews with six cross-divisional informants, field observation during actual pitching conditions, and documentation including pitching invitations, client briefs, and proposals. Internal capabilities were analyzed using the McKinsey 7S Framework and evaluated using VRIN criteria from a Resource-Based View (RBV) perspective. Findings reveal that three elements, Staff, Skills, and Shared Values, consistently satisfy all VRIN criteria and form the core of the company's sustainable competitive advantage, while Structure and Systems remain generic and informal, making them operational vulnerabilities. DAMN! Inc's competitive advantage stems from a capability configuration that is complementary and causally ambiguous to outsiders, making it difficult for competitors to replicate as a whole. This study recommends standardizing the cross-divisional brief handover process and formalizing the pitching workflow SOP as steps toward sustained strengthening of the company's competitive position.